A GIS-based multi-tier framework for assessing the ecological potential of urban vacant land - Izyan Ayuni Mohamad Selamat; Sreetheran Maruthaveeran; Mohd Johari Mohd Yusof; Mohd Fairuz Shahidan (Urban Science, 2025)
Urban vacant land possesses significant yet untapped ecological potential (capac- ity to support biodiversity, ecological processes, and ecosystem functions) for enhancing urban sustainability and resilience. However, the absence of structured and adaptable frameworks for ecological assessment limits its effective integration into urban planning. This study introduces a novel multi-tier ecological assessment framework, combining expert-driven criteria established through the Fuzzy Delphi Method with GIS-based spatial analysis. The framework ensures flexibility and scalability, enabling planners to perform rapid preliminary assessments and progressively detailed evaluations depending on avail- able resources and specific planning objectives. A case study in Sentul-Manjalara, Kuala Lumpur, demonstrates the framework’s practical application, resulting in an ecological potential map categorising vacant parcels into high, medium, and low revitalisation priori- ties. This approach effectively connects theoretical ecological insights and actionable urban planning, providing policymakers and planners with an evidence-based decision-making tool for strategically prioritising vacant land revitalisation efforts. The outcome enhances urban biodiversity, ecological connectivity, and long-term urban resilience.